Judging scientific information: Does source evaluation prevent the seductive effect of text easiness?. (October 2019) - Scharrer, Lisa; Stadtler, Marc; Bromme, Rainer
Abstract: Although nonexperts usually lack sufficient topic knowledge and experience, they can be "seduced" into relying on their direct evaluation of scientific content, particularly when encountering information that is relatively easy to comprehend. Two experimental studies tested whether this easiness effect can be prevented if readers can lean on evaluations of source credibility instead. In both studies, medical nonexperts read Internet texts about different health topics and evaluated the contained claims. The texts were either more comprehensible or less comprehensible, and they were supposedly authored by either a more credible or a less credible source. Experiment 1 demonstrated that nonexperts (i.e., 48 undergraduate students) agreed more strongly and confidently with claims from a more credible compared to a less credible source. However, the influence of source credibility did not prevent the easiness effect: Participants also agreed more strongly and confidently with claims from more comprehensible texts compared to less comprehensible texts. The same pattern of results emerged in Experiment 2 (with 53 undergraduate students), where source credibility was manipulated more strongly. Although source credibility had a greater effect on nonexperts' claim judgment than in Experiment 1, readers still agreed more strongly and confidently with claims from more comprehensible than less comprehensible texts. Results of both studies suggest that nonexperts are not sufficiently aware of the relative importance of source evaluation, which may increase their susceptibility to misinformation. Highlights: Easy science text comprehension seduces nonexperts to rely on their own evaluations. The easiness effect persists even if nonexperts can assess source credibility instead. This indicates a lacking awareness of the relative importance of source evaluation. Raising awareness of nonexperts' epistemic limits may prevent the easiness effect.